Regulation of CD8 T cell by B-cells: A narrative review - Van Meerhaeghe, Tess; Néel, Antoine; Brouard, Sophie; Degauque, Nicolas (Frontiers in Immunology, 2023)
Activation of CD4 T cells by B cells has been extensively studied, but B cell-regulated priming, proliferation, and survival of CD8 T cells remains controversial. B cells express high levels of MHC class I molecules and can potentially act as antigen-presenting cells (APCs) for CD8 T cells. Several in vivo studies in mice and humans demonstrate the role of B cells as modulators of CD8 T cell function in the context of viral infections, autoimmune diseases, cancer and allograft rejection. In addition, B-cell depletion therapies can lead to impaired CD8 T-cell responses. In this review, we attempt to answer 2 important questions: 1. the role of B cell antigen presentation and cytokine production in the regulation of CD8 T cell survival and cell fate determination, and 2. The role of B cells in the formation and maintenance of CD8 T cell memory.